"Men Always Adopt": Infertility and Reproduction From a Male Perspective. (August 2013) - Herrera, Florencia
The purpose of this article is to understand how men who have faced difficulties in conceiving with their partners and have become fathers by means of nonnormative modes of reproduction see and portray themselves in the reproductive process. Narratives by 16 fathers who resorted to assisted reproduction and/or adoption are analyzed and compared in order to learn how they describe their participation in these processes. Unstructured interviews that favor the emergence of narratives describing men's experience in reproduction processes were conducted. In men's assisted reproduction narratives, men portray themselves as secondary and nonactive characters. By contrast, in narratives about adoption, men center themselves as co- or equal actors. Becoming fathers is a central aspect of Chilean men's lives and identities. However, they are still looking for ways to validate their position in the reproductive process.